Prevalence of Xanthomonas euvesicatoria on Pepper in Brazil - Areas, Maysa Souza [UNESP]; Gonçalves, Ricardo Marcelo [UNESP]; Soman, José Marcelo [UNESP]; Sakate, Renate Krause [UNESP]; Gioria, Ricardo; Silva Júnior, Tadeu Antônio Fernandes da [UNESP]; Maringoni, Antonio Carlos [UNESP] (Blackwell Verlag GmbH, 2014)
Bacterial spot, caused by Xanthomonas spp., is one of the major diseases ofpepper in Brazil, causing considerable losses to crop productivity. The efﬁcient management of the disease is hampered by the high variability ofthe causal agents. In Brazil, there is no knowledge of which species of Xanthomonas occurs on pepper. In this study, 59 strains of Xanthomonasspp. isolated from different pepper-producing regions of Brazil were characterized by biochemical and molecular techniques. Results showed theprevalence of X. euvesicatoria as the causal agent of bacterial spot onpepper in Brazil.
Keywords: Bacterial spot; Biochemical and molecularcharacterization; Capsicum annuum